Effect of Mix Culture Bacteria and Fungi in Fermented Peanut Hulls-Based Feed Supplement on Physical Quality and In Vitro Rumen Fermentation Parameters - DELA RIA NESTI; Ahmad Baidlowi; Achmad Fauzi; Ida Tjahajati (Jurnal Ilmu Ternak dan Veteriner, 2020)
The purpose of this research was to determine the effect of the combination of mix culture bacteria (EM4®:E) and fungi (Trichoderma viridae:TV) on physical quality and in vitro rumen fermentation parameters of peanut hull-based feed supplements. Basal feed was divided into four treatments, which were: P0 (BF); P1 (E:25%+TV:75%); P2 (E:50%+TV:50%),; and P3 (E:75%+TV:25%); and each treatment had three replications. Feeds were fermented facultative anaerobically for nine days. The observed parameters were physical qualities (color, odor, fungi appearance and pH), and in vitro rumen fermentation parameters (rumen pH, microbial protein content, and total volatile fatty acid content). Data were analyzed using one way ANOVA design, and the significance of differences were tested using Kruskall-Wallis test for the physical qualities data and Duncan’s New Multiple Range Test (DMRT) test for in vitro rumen fermentation parameters. Results showed that the combination of E and TV at different level did not affect odor and the fungi appearance parameters (P≥0.05), however, it significantly affected P≤0.05) color change from blackish (1.64) in P0 to brownish in P1, P2 and P3 of 2.44; 2.69; and 2.80, respectively. The pH also decreased significantly (P≤0.05) by 10.67%.  Treatment also did not affect the rumen pH, microbial protein content, and total volatile fatty acid content (P≥0.05). It is concluded that the combination of the EM4® 25%: Trichoderma viridae 75% on peanut-hull based feed supplement fermentation gives the best result on color and pH fermented feed product without affecting the rumen fermentation process.